Following Spinal Cord Injury Transected Reticulospinal Tract Axons Develop New Collateral Inputs to Spinal Interneurons in Parallel with Locomotor Recovery. (12th September 2017) - May, Zacnicte; Fenrich, Keith K.; Dahlby, Julia; Batty, Nicholas J.; Torres-Espín, Abel; Fouad, Karim
Abstract : The reticulospinal tract (RtST) descends from the reticular formation and terminates in the spinal cord. The RtST drives the initiation of locomotion and postural control. RtST axons form new contacts with propriospinal interneurons (PrINs) after incomplete spinal cord injury (SCI); however, it is unclear if injured or uninjured axons make these connections. We completely transected all traced RtST axons in rats using a staggered model, where a hemisection SCI at vertebra T10 is followed by a contralateral hemisection at vertebra T7. In one group of the animals, the T7 SCI was performed 2 weeks after the T10 SCI (delayed; dSTAG), and in another group, the T10 and T7 SCIs were concomitant (cSTAG). dSTAG animals had significantly more RtST-PrIN contacts in the grey matter compared to cSTAG animals (p < 0.05 ). These results were accompanied by enhanced locomotor recovery with dSTAG animals significantly outperforming cSTAG animals (BBB test; p < 0.05 ). This difference suggests that activity in neuronal networks below the first SCI may contribute to enhanced recovery, because dSTAG rats recovered locomotor ability before the second hemisection. In conclusion, our findings support the hypothesis that the injured RtST forms new connections and is a key player in the recovery of locomotion post-SCI.